PEMODELAN PEMASANGAN PENYANGGA SEMENTARA MENGGUNAKAN PERANGKAT LUNAK PHASE 2 PADA HEADRACE TUNNEL CHAINAGE 45 M â 155 M DI PLTA TULIS KABUPATEN BANJARNEGARA, JAWA TENGAH - Mahmud, Ghozali (Geological Engineering E-Journal, 2013)
In the process of tunnel construction, the support design process is a very important thing to do. This process must be done carefully and thoroughly in order to obtain cost efficiencies expenditureon the tunnel project. Because the total expenditure in the construction of a tunnel is not cheap. This support planning process itself is divided into two namely the planning of temporary andpermanent support. The support planning usually is done before and the time of tunnelconstruction. This research aims to model the geological conditions around the tunnel, the tunnel pit conditions before supporting system installed, and the temporary support design of theheadrace tunnel of Tulis Hydropower Banjarnegara Residence, Central Java Province. So we willknow types of the most appropriate support based on physical properties, rock mechanics and rock mass behavior along the tunnel. The research method used is descriptive and experimentalmethods. By way of temporary support modelling in headrace tunnel with Phase2 software . In thisresearch will analyze and make temporary support models of 45 m â 155 m chainage the headrace tunnel. In the chainage will be made 3 models (II b, III a, and III b) based on rock mass ratingvalue Based on the modelling results it is known that for class II b has a total displacement of < 5mm. So the installation of supports on class II b is relatively stable and secure there will be no collapse of the tunnel. As well as combinations obtained temporary support is most effective with atotal value that is the smallest displacementnya shotcrete 1 variations is 50 mm; 3 m long of rockbolts with spaced 2 m and 10 of its number ; shotcrete 2 variations 100 mm. Whereass the rock mass class III A and III B have > 5 mm in the result of total displacement. So the tunnel is will notstable and secure with a variety of shotcrete and rock bolts that has been done. It would requirethe addition of another temporary support variant form of steel set as installation instructions and supporting the tunnel excavation (After Bieniawski, 1989).